Retrospection and Reflection on the Role of Henry C. Lu as a Traditional Chinese Medicine Writer, Educator, and Translator - Xiao-Li Li; Li-An Ma; Qing Wu (Wolters Kluwer Health/LWW, 2022)
This paper respectfully commemorates the life of Dr. Henry C. Lu (1936-2022), who was the founding president of International College of Traditional Chinese Medicine of Vancouver. Dr. Lu was an active educator, a prolific writer and translator of traditional Chinese medicine (TCM) in the West and an influential figure during the initial stage of the international dissemination of TCM. By comprehensively searching, referencing, and cross-validating the literature, this article reviewed Dr. Lu's major life events, bibliography, and, most importantly, his contribution to TCM education and translation. Dr. Lu should be given more credit for his achievements, and further studies are needed in future.